PENGEMBANGAN MULTIMEDIA INTERAKTIF KARAKTERISTIK TATA SURYA (KATARYA) KELAS VI SEKOLAH DASAR - Naufal Daffa Atha; Wawan Priyanto; Husni Wakhyudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background that prompted this research was students' difficulties in following and understanding science lessons on the solar system. However, after further investigation through questionnaires, interviews, and needs analysis, the underlying problem was revealed to be a lack of teacher innovation in the learning process using instructional media. Teachers still use conventional learning techniques, focusing primarily on textbooks as learning resources. This leads to student boredom during the learning process The research questions are: 1) How does the development of interactive multimedia on the characteristics of the solar system (KATARYA) for sixth grade elementary school students based on Articulate Storyline work? 2) How is the feasibility of developing interactive multimedia on the characteristics of the solar system (KATARYA) for sixth grade elementary school students based on Articulate Storyline? 3) How is the practicality of developing interactive multimedia on the characteristics of the solar system (KATARYA) for sixth grade elementary school students based on Articulate Storyline? This research method is Research and Development (R&D). The ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model was used. Data collection techniques included observation, interviews, questionnaires, and documentation. Product testing was conducted at Muhammadiyah 16 Elementary School, Semarang. Based on the research conducted, the media validation score was 93%, categorized as